Fitting In Affordable Housing in Downtown Toronto - Teti Armiati Argo (Journal of Regional and City Planning, 1998)
Allocating new low income housing could be challenging particularly in large cities which emphasize profit-making activities. For urban planners in Toronto, selling up government interventions should be conjoined with the Ontario's policy on low income housing, but more importantly, with the nature of provincial politics. When socialist"”oriented government took power social spending was protected from the provincial budget cut which represent favorable policies and commitments to wards the needy and disadvantaged. It was a bad decision especially in the period of recession. Unpopular to the majority, the conservative"”oriented party easily won seats at the provincial-based power. They prefer market-oriented, strong"”handed policies on low-income and provision of the basic needs to the needy, leaving among other low Income housing to market mechanism to determine the size of low income housing. This leads planners to rely heavily on the non"”interventive instruments to provide such housing.